Karakteristik Dewan Direksi dan Pengungkapan Emisi Karbon - Nabilla Khansya; Maylia Pramono Sari (Universitas Katolik Soegijapranata Semarang, 2026)
This study analyzes the effects of gender diversity on the Board of Directors, the educational background of the Board of Directors, and the size of the Board of Directors on carbon emissions disclosure and tests the role of firm size as a moderating variable. Climate change issues are increasing external pressure and demands on companies to promote transparency in carbon emissions disclosure, although in practice this is still influenced by internal firm factors. The sample of companies was drawn from energy sector firms listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Data were analyzed using moderated regression analysis (MRA). The results indicate that Board gender diversity has a positive effect on carbon emissions disclosure, whereas Board education and Board size do not affect carbon emissions disclosure. Furthermore, firm size can weaken the effect of Board gender diversity on carbon emissions disclosure. These findings highlight the importance of external factors and the strengthening of corporate sustainability reporting policies and systems in enhancing environmental information transparency. Practically, this study suggests that companies should optimize the role of the Board of Directors in responding to stakeholder demands through strengthened corporate governance and clear government policy support, thereby improving the transparency and quality of carbon emissions disclosure.